The Role of Profitability in Mediating the Effect of Corporate Social Responsibility on Firm Value - Juliasari, Deni; Ana, Selvia Roos; Yulianti, Ani; Heni, Heni; Cahyaningati, Retno (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This research seeks to investigate the impact of Corporate Social Responsibility (CSR) on firm value, with profitability examined as a mediating variable. Employing a quantitative explanatory approach, the study uses purposive sampling as its sampling technique. The sample comprises 15 energy sector companies listed on the Indonesia Stock Exchange between 2021 and 2023, yielding a total of 45 firm-year observations. The analytical methods involve panel data regression and mediation analysis using the Sobel test. The findings reveal that CSR does not have a significant influence on profitability, nor does it directly affect firm value. However, profitability is found to have a significant effect on firm value. Furthermore, CSR is not shown to impact firm value indirectly through profitability. Although CSR is often regarded as a strategic initiative aimed at enhancing corporate image and fostering long-term sustainability, the results suggest that within the context of energy companies during the observed period, CSR activities have not generated sufficient financial benefits to boost profitability, and consequently, do not contribute meaningfully to the enhancement of firm value.